User Access Control and Authentication System for VoIP Service in Mobile Communication Environments - Ho-Kyung Yang; Jeong-Kyung Moon; Cheol-Rim Choi; Hwang-Bin Ryou (International Journal of Distributed Sensor Networks)
VoIP, which is used to transmit voice data on the Internet, is being welcomed as a replacement for the PSTN. In VoIP, voice data are converted to IP data and transmitted in an ordinary IP network. As a result, it is less expensive than the ordinary telephone network and has excellent scalability. With the increasing demand for VoIP services, problems are also occurring, namely, security vulnerabilities and degraded service quality. To address these issues, in this paper an AA (Attribute Authority) server is added to VoIP to design an authentication system with bolstered security and differentiated user access.